Two phase natural convection: CFD simulations and PIV measurement - Gandhi, Mayurkumar S.; Sathe, Mayur J.; Joshi, Jyeshtharaj B.; Vijayan, Pallippattu K. (Chemical engineering science, 2011)
Buoyancy induced flow and heat transfer are important phenomena in a wide range of engineering systems e.g. electronics and photovoltaics cooling, thermosiphon heat exchangers, solar-thermal heat absorbers, passive decay heat removal systems, etc. Such systems are subject to thermal stratification. The objective of the present work is to study the single phase and two phase (boiling) natural convection accompanied by thermal stratification. We carried out velocity and temperature measurements in a rectangular tank (0.8×0.6×0.6 m 3) fitted with (a) a central tube, and (b) a 10 tube assembly; which form the heat transfer surface. Flows were measured using Particle Image Velocimetry (PIV). Additionally, computational fluid dynamic (CFD) simulations of these systems were performed: first with an assumption of no-boiling (i.e. no phase change) near the heat transfer surfaces; for which we used the open source CFD code OpenFOAM-1.6. For two phase simulations, we used the boiling model of Ganguli et al. (2010) and carried out simulations using the commercial software FLUENT 6.3. The extent of stratification and mixing has been investigated for a range of Rayleigh numbers from 4.34×10 11 to 2.59×10 14. The flow information obtained from PIV was analyzed for insights into the dynamics of turbulent flow structures. We used the signal processing technique of discrete wavelet transform (DWT) for this purpose. From the analysis, we were able to estimate the size, velocity and energy distribution of turbulent structures in our flows. This information was used to estimate wall heat transfer coefficients. A good agreement was observed between the predicted and the experimental values of heat transfer coefficients.